The last ridge : [videorecording (DVD)] : the uphill battles of the 10th Mountain Division - Kealy, Abbie, 1955-; Simon, Scott; Jenkins, McKay, 1963- (Janson Media, 2008)
Chronicles the remarkable story of the legendary alpine fighting force known as the U.S. Army's 10th Mountain Division. Their claim to fame began during World War II when the U.S. Army advanced on the Germans who were entrenched in Italy's heavily fortified mountaintops. After a large loss, the U.S. Army brass calls in the 10th. Also look at the current 10th as it continues the legacy.